Closed casket [compact disc, unabridged] - Hannah, Sophie, 1971-; Christie, Agatha, 1890-1976 (Harper Audio, 2016)
Lady Athelinda Playford -- one of the world's most beloved children's authors -- springs a surprise on the lawyer entrusted with her will. As guests arrive for a party at her Irish mansion, Lady Playford has decided to cut off her two children without a penny . . . and leave her vast fortune to someone else: an invalid who has only weeks to live.